Absence of mutations in the interspecies conserved regions of the CFTR promoter region in cystic fibrosis (CF) and CF related patients. Issue 2 (February 1998) - Verlingue, C; Vuillaumier, S; Mercier, B; Le Gac, M; Elion, J; Férec, C; Denamur, E
Abstract : This study was aimed at testing if a 5.2 kb untranslated region on both sides of the first CFTR exon, shown to contain regulatory elements, could carry mutations responsible for cystic fibrosis (CF) or CF related phenotypes. Selection of the DNA segments studied within this region was based upon the identification of conserved sequences throughout evolution (phylogenetic footprints, PFs). Comparison of the CFTR sequences in eight species representing four orders of mammals (man, gibbon, rhesus monkey, squirrel, monkey, rabbit, cow, rat, and mouse) identified four clusters of PFs within the 3.9 kb of DNA sequence upstream from the initiation codon, as well as two nearby PFs at +1 kb within intron 1. Six DNA segments containing PFs were scanned for mutations by denaturing gradient gel electrophoresis (DGGE) in patients with CF (n = 29), congenital bilateral absence of the vas deferens (n = 143), or disseminated bronchiectasis (n = 33), for whom only one or no mutations had been identified despite extensive DGGE analysis of the 27 CFTR exons and exon/intron boundaries. Only one polymorphism (-966 T–>G) was identified with a frequency of 2.2% and no other sequence variations were found. This study reinforces the idea that the promoter region in the CFTR is not frequently mutated.